Pengembangan Media Pembelajaran Video Animasi Pada Materi Drama Siswa Kelas VIII SMP Negeri 2 Palembang - Nadia Asrobanni; Dessy Wardiah; Hetilaniar Hetilaniar (Journal on Education, 2023)
This study aims to produce animated video learning media on drama material for class VIII students of SMP Negeri 2 Palembang. This Research and Development follows the working steps of the ADDIE development model. The test subjects in the study were class VIII.3 students at Palembang 2 Public Middle School with a total of 10 students for small-scale group trials and 35 students for large-scale field trials. Based on the results of the study, it was shown that the animated video learning media product in the resulting drama material fulfilled the feasibility aspect of the material with a very valid presentation value of 100% and the language feasibility aspect was in a very valid category with a very valid percentage of 91% and the media feasibility aspect with a very valid percentage of 100% valid. So it can be concluded that the animated video learning media developed obtains an average percentage of 97% indicating a very valid and feasible category to use.